1989
DOI: 10.1111/j.1469-8137.1989.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal mediation of competition between coniferous tree species

Abstract: SUM MARYTo test the effect of ectomycorrhizal fungi (1"'MF) on interactions between host plants, Pseiidotsuga mcnzicsii (Mirb.) Franco and Piinis potidcrosa Dougl. ex. Laws., seedlings were grown in replacement series in pasteurized soil with (a) no EMI"' added, (/;) two EMF species added -Rhizopogon vinicotor Smith (specific to Douglas-Hr) and R. octiraceortibens Smith (specific to pine), and (c) four EMF species added -the two Rhizopogon species plus two host generalists, Laccaria toccata (Scop, ex Fr.) Bk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
80
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 25 publications
(7 reference statements)
2
80
0
2
Order By: Relevance
“…It is known that the presence of particular mycorrhizal species in a given soil can facilitate the establishment of plant species that benefit from that fungus in that soil (4,8,18,25,35,36,51,55,59). There are also many examples of relationships between mycorrhizal fungal infection by specific fungal species and the growth rate and/or competitive dynamics of particular plant species (6,12,36,38,43,54,55) and ECM or plant ability to acquire N and other nutrients (16,21,35). Previously, Nara (35) demonstrated that different fungal inoculants can have various effects on seedling growth and N acquisition under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the presence of particular mycorrhizal species in a given soil can facilitate the establishment of plant species that benefit from that fungus in that soil (4,8,18,25,35,36,51,55,59). There are also many examples of relationships between mycorrhizal fungal infection by specific fungal species and the growth rate and/or competitive dynamics of particular plant species (6,12,36,38,43,54,55) and ECM or plant ability to acquire N and other nutrients (16,21,35). Previously, Nara (35) demonstrated that different fungal inoculants can have various effects on seedling growth and N acquisition under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show better performance, for example, of EM-mycorrhizal than non-mycorrhizal planted Douglas fir seedlings (e.g., Villeneuve, Le Tacon & Bouchard, 1991). In addition to rapid mycorrhizal infection, hyphal links to larger, established trees might benefit neighbouring seedlings through direct transfer of organic nutrients (e.g., Finlay & Read, 1986;Arnebrant et al, 1993), increased access to inorganic nutrients or water in a greater volume of soil (Eissenstat & Newman, 1990), and alteration of the balance of plant-plant interactions (e.g.. Perry et al, 1989;Perry, Bell & Amaranthus, 1992). Conifer seedlings planted near an established tree might also form a greater diversity and different EM types than those planted in isolation.…”
mentioning
confidence: 99%
“…Furthermore, the connection between mycorrhizal fungi and their host trees cannot be easily established because many fungi are promiscuous and can receive C from several species of trees (2,7,8). Such fungi form hyphal links transferring C and nutrients between plants and can thus influence plant competition (2,(7)(8)(9)(10). Recently, it was suggested, after feeding one seedling with 14 CO 2 and one with 13 CO 2 , that there was a net transfer of C from one seedling to another via mycorrhizal connections (8).…”
mentioning
confidence: 99%